Does Gender Diversity among the Board of Directors Significantly Affect a Company’s Financial Performance? - Ariadi, Deni; Serly; Susanto, Androni (Jurnal Manajemen, 2024)
In recent years, the issue of women’s representation on corporate boards has gained considerable attention. The presence of women on boards is believed to enhance their effectiveness. This study aims to investigate whether the gender composition of corporate boards plays a crucial role in the financial performance of the manufacturing sector, which is a significant contributor to Indonesia’s economic growth. Purposive sampling led to the selection of 85 companies that met the criteria, resulting in a total sample of 680 companies over an eight-year period. Gender diversity is assessed using the proportion of female directors, while financial performance is measured by Tobin’s Q. Additionally, six control variables are included in this study, namely the board of commissioners, board size, firm size, leverage, age, and market value. The analytical data calculations were conducted using STATA 13 software to ensure more precise results. The results from the regression tests reveal a significant positive impact of gender diversity on financial performance, both with and without the control variables. Furthermore, these findings provide support for two prominent theories: agency theory and resource dependence theory.